Self-Allocation in Contests - Axel Bernergard; Karl Wärneryd (Center for Economic Studies and ifo Institute (CESifo), 2017)
We consider contestants who must choose exactly one contest, out of several, to participate in. We show that when the contest technology is of a certain type, or when the number of contestants is large, a self-allocation equilibrium, i.e., one where no contestant would wish to change his choice of contest, results in the allocation of players to contests that maximizes aggregate equilibrium effort. For a class of oligopoly models that are equivalent to contests, this implies output maximization.
Keywords: C72; D43; D44; D72; D74; L13; 330; contests; self-allocation; effort maximization; quantity competition